The competitiveness of African coffees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
African coffees are steadily losing their competitive edge vis-\E0-vis their Latin American and South-east Asian rivals. Two specialists, Benoit Daviron of the Centre de coop\E9ration internationale en recherche agronomique pour le d\E9veloppement...